Ventilation of the Black Sea pycnocline on seasonal and interannual time scales - IVANOV, L.I.; BELOKOPYTOV, V.N.; OZSOY, E.; SAMODUROV, A.S. (Mediterranean Marine Science, 2000)
The paper is a description of temporal variability of winter cooling conditions and estimation of effective cross-isopycnal mixing rates in the Black Sea. Data averaging versus salinity / sigma-t scale was used to filter effects of local dynamics. It is shown that traces of winter mixing events appear well preserved in the temperature-salinity structure, due to the peculiarities of the Black Sea where temperature often acts as a passive tracer with a smaller contribution to density as compared to salinity. Vertical distribution of the magnitudes of temperature oscillations indicates that the convection events have limited effects in modifying the structure of the middle and lower pycnocline on a seasonal time scale. However, long-term fluctuations are well recognised. The magnitudes of the seasonal and long-term temperature fluctuations are comparable only in the upper pycnocline. Three major cooling events can be distinguished from the record of the pycnocline temperature for the past 75 years. The intensive cooling occurred in the late 1920s - early 1930s, early 1950s and late 1980s - early 1990s. Partial renewal of the water of the cold intermediate layer core took place approximately once in two years. The period when convection causes erosion of the pycnocline lasts for only a week. It is shown that a lateral source of heat and salt exists for the upper pycnocline, where it is the cold intermediate water, and for the lower pycnocline, the layer below S@ 20.5, where this lateral source of salt and heat is maintained by disintegrating Bosphorus plume.